Reverse logistics in plastics subsector: main facilitators and barriers (2015)
Industrial solid waste (ISW) is increasing in both quantity and complexity and it is a priority to establish strategies to manage it. Reverse Logistics (RL) is a strategy that enables material recovery and reuse avoiding the damage that ISW may cause; also RL organizes solid waste management activities and supports other activities such as ISW trading. Most of the research linking ISW and RL in developed countries is related to the electronics subsector because of the negative effects on the environment; however, research oriented towards plastics subsector waste is lower. This is the case in Colombia where the plastics subsector is composed mainly by small and medium-sized enterprises (SMEs) facing diverse constraints for their operation. Main facilitators and barriers that face SMEs in the Colombian plastics subsector to undertake RL programs were identified. An exploratory study was carried out in which business managers assessed the facilitators and barriers identified in the literature. The results showed that the availability of skilled people to perform RL activities is one of the most important internal facilitators and the lack of secondary markets for recovered materials is among the external barriers. The findings contribute to the body of knowledge in the field that is still maturing in Colombia.